The effectiveness of nicotine replacement therapies in smoking cessation. - Silagy, C; Mant, D; Fowler, G; Lodge, M (1994)
OBJECTIVE: To determine the effectiveness of nicotine replacement therapies (NRTs) (including gum, transdermal patch, intranasal spray, and inhaled preparations) in facilitating smoking cessation, and to determine whether the effect was influenced by the clinical setting in which the smoker was recruited and treated, the level of nicotine dependency, the dosage of NRT used, or the intensity of additional advice and support offered to the smoker. DATA SOURCES: Published trials of NRT were identified by a systematic search of 7 electronic databases, published reviews, reference lists from clinical trials, conference abstracts, smoking and health bulletins, and a bibliography on smoking and health. Unpublished trials were identified by approaching manufacturers of NRT. STUDY SELECTION: A total of 53 trials (42 gum, 9 patch, 1 intranasal spray, and 1 inhaler), with data from 17,703 patients, were included in the analyses. Only trials that assessed abstinence at least 6 months after the commencement of therapy were included. DATA EXTRACTION: Data were extracted from the trial reports by 2 authors independently. Where the methodology was unclear or the results were not expressed in a form which allowed extraction of key data we wrote to the investigators for the required information. DATA SYNTHESIS: Use of NRT increased the odds ratio (OR) of abstinence to 1.71 (95% confidence interval [CI], 1.56 to 1.87) compared with those who had been allocated to the control interventions. The OR for the different forms of NRT were 1.61 for nicotine gum (95% CI, 1.46 to 1.78), 2.07 (95% CI, 1.62 to 2.62) for transdermal patch, 2.92 (95% CI, 1.49 to 5.74) for nasal spray, and 3.05 for inhaled nicotine (95% CI, 1.42 to 6.57). These odds were not significantly higher in patients with higher levels of nicotine dependence (Fagerstrom score > or = 7; P = 0.06), but they were largely independent of the intensity of additional support provided or the setting in which the NRT was offered. CONCLUSION: We conclude that the currently available forms of NRT are effective therapies to aid smoking cessation.